PENERAPAN PRINSIP BAGI HASIL DAN PENGARUHNYA TERHADAP KEPUTUSAN MENABUNG PADA NASABAH BANK MUAMALAT KANTOR CABANG MADIUN - Novita Erliana Sari; Nik Amah; Yahya Reka Wirawan (PROMOSI: Jurnal Program Studi Pendidikan Ekonomi, 2017)
Public understanding of sharia banks is often only based on the difference with conventional banks. Conventional banks use interest systems while Islamic banks use the principle of profit sharing. Implementation of the application of profit sharing becomes the factor that determines the decision of the customer to save at Bank Muamalat Branch of Madiun. This study aims to determine the application of the principle of profit sharing to the decision to save at Bank Muamalat Branch of Madiun. The population in this study is all customers of Savings Bank products Muamalat Branch of Madiun. The sampling technique uses probability sampling. This research type is quantitative research.